Study guides

Q: What is 5p 15p plus 7p in algebra?

Write your answer...

Submit

Related questions

-3p

7p + 2 = 5p + 8 7p - 5p = 8 - 2 2p = 6 p = 3

5p + 4y

5p-7q

4p + 9 + (-7p) + 2 = 4p - 7p + 9 + 2 = -3p + 11

6nx + 7p - 14p + 2nx + 6x = 8nx - 7p + 6x

-7p2 -2p3 + 5 is an expression, not an equation or inequality. An expression cannot be solved

2p+7p = 9p simplified

7p+5q=-3, p=1 7Xp+5q=-3 7+5q=-3 5p=-10 p=-2

4p + 9 - 7p + 2 4p - 7p + 9 + 2 p(4 - 7) + 9 + 2 -3p + 11

8p+5 = 11+7p= 8p-7p = 11-5p = 6

14 + 6p = 6 + 7p 8 = p

4p+9-7p+2 -3p+11 p = 11/3

7p+5t

Collect like terms together: 4p + 9 + 7p + 2 = (4p + 7p) + (9 + 2) = (4 + 7)p + 11 = 11p + 11 = 11(p + 1)

-7p + 5r - 6p + 3r = -7p - 6p + 5r + 3r = -(7 + 6)p + (5 + 3)r = -13p + 8r

7p+2 is an algebraic expression. Since it is neither an equation nor an equality, it cannot have a solution or answer.

11p+11

15 + 3 = 7p - 4p ie 18 = 3p so p = 6

7p + 2q = 46 . . . . (A) 5p + 3q = 36 . . . . (B) 3*(A): 21p + 6q = 138 2*(B): 10p + 6q = 72 Subtracting gives 11p = 66 so that p = 6 Substitute for p in (A): 7*6 + 2q = 46 or 42 + 2q = 46 which gives 2q = 4 so that q = 2 Solution: (p, q) = (6,2)

p=-3

8m(4 + 7p)

(3q + 2p)(9q + 7p)

8p-p-4p= 7p-4p= 3p

7p-10p = -3

People also asked